2013
DOI: 10.1155/2013/607109
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant and Wound Healing Potentials ofSphaeranthus amaranthoidesBurm.f.

Abstract: Background. Sphaeranthus amaranthoides commonly known as sivakaranthai is used in folklore medicine for the treatment of skin diseases. Methods. The antioxidant activity of the extract and its fraction was evaluated by using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity, total antioxidant capacity, and total phenolic content. The tested plant extracts showed variable degrees of antioxidant activity. In the present study, methanolic extract of the whole plant of S. amaranthoides and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 22 publications
(21 reference statements)
4
47
0
1
Order By: Relevance
“…Antioxidant compounds reduce the free radicals and pus in the wound area, thereby healing the wound completely . Other papers have reported that the medicinal plants and their extraction rich in anti‐inflammatory and antioxidant compounds significantly decrease the production of pus and enhance the wound healing process . Our study indicated that TiNPs @Ziziphora had a strong antioxidant activity.…”
Section: Resultssupporting
confidence: 56%
“…Antioxidant compounds reduce the free radicals and pus in the wound area, thereby healing the wound completely . Other papers have reported that the medicinal plants and their extraction rich in anti‐inflammatory and antioxidant compounds significantly decrease the production of pus and enhance the wound healing process . Our study indicated that TiNPs @Ziziphora had a strong antioxidant activity.…”
Section: Resultssupporting
confidence: 56%
“…Further, presence of free radicals in the wound site may increase the amount of pus . Antioxidant compounds reduce the free radicals and pus in the wound area, thereby healing the wound completely . Other papers have reported that the medicinal plants and their extraction rich in anti‐inflammatory and antioxidant compounds significantly decrease the production of pus and enhance the wound healing process .…”
Section: Resultsmentioning
confidence: 99%
“…Further, the presence of free radicals in the wound site may increase the amount of pus . Antioxidant compounds decrease the free radicals and pus in the wound area, thereby healing the wound completely . Other researchers have reported that medicinal plants and their extracts rich in anti‐inflammatory and antioxidant compounds significantly reduce the production of pus and increase the wound healing process .…”
Section: Resultsmentioning
confidence: 99%